Digital-Based Edupreneurship among Senior High School Students - Muhammad Rakib; Nur Halim; Andika Isma; Hajar Dewantara; Muhammad Jufri; Sitti Hajerah Hasyim (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
The problems experienced by partners are as follows: (1) Students do not have good knowledge of the basic concepts of digital marketing, (2) Students do not have the knowledge and technical skills to identify digital-based marketing elements well, (3) Students do not yet have the knowledge and skills to create attractive copywriting, and (4) Students do not yet have the knowledge and skills to use Google My Business in promoting/advertising products. This community service program will be implemented from February 2024 to October 2024, starting from the preparation stage, namely observing and collaborating with partners, preparing PKM proposals, implementing training, monitoring and evaluation, and reporting. The number of training participants includes student representatives or student organization administrators at SMA Negeri 11 Sidenreng Rappang. The methods used are lectures, discussions, questions and answers, practice and mentoring. Procedures for carrying out activities are pre-test and post-test, presentation of material, practice and mentoring. To measure the level of success of this activity program, it is carried out by measuring; (1) the level of Partner participation, (2) the level of activity of the training participants, and (2) the level of knowledge and skills of the training participants. The data analysis technique uses descriptive statistical analysis. The results of the service implementation are (1) Students have good knowledge of the basic concepts of digital marketing, (2) Students have knowledge and technical skills to identify digital-based marketing elements well, (3) Students have knowledge and skills in making copywriting. interesting, and (4) Students have the knowledge and skills to use Google My Business in promoting/advertising products.